Pelatihan Diversifikasi Produk dan Strategi Digital Marketing untuk Meningkatkan Pendapatan Masyarakat Kelurahan Penanae Kota Bima - Nurul Huda; Jaenab; Sarina; Iko Saputra; Nurbaity Raodatun Nadita (Indo Publishing, 2025)
This community service aims to increase the knowledge and skills of community business groups through the transformation of packaging technology, marketing and business management by diversifying the basic ingredients of duck eggs, jackfruit, cassava, moringa leaves and corn into processed smoked salted egg products. Community skills in processing duck eggs and other natural products already exist but there is not yet a variety of product types. The aim of this program is to form a new business unit that develops food products from duck egg ingredients and uses online marketing strategies. Specifically, this program trains corporate participants to produce various types of processed products from duck eggs. The training starts with processing, packaging, marketing methods and ends with demonstrations, training or counseling. This activity involves members of students studying real work who are accompanied by accompanying lecturers in the management study program, the Penanae sub-district apparatus with business actors in the Penanane sub-district and the community in Penanae sub-district, Bima city. As a result of this activity, business actors have understood skills and entrepreneurship, know how to manage a business, have understood and have skills and entrepreneurship, know how to manage a structured business, have smoked salted egg processed products, and understand how to market products with packaging innovation and the use of technology. Understanding of duck egg processing among business actors is increasing and opening the minds of business actors to take advantage of existing advantages to increase income. Active business actors respond positively to the skills and knowledge conveyed through team dedication.